Personal Life in the Context of Globalization - Le Thanh Hoa (MultiTech Publisher, 2024)
The purpose of this study is to clarify the role of the individual in social life; each individual is not only a subject of cognition but also an object of cognition in the context of globalization. To achieve the above purpose, the author uses the methodology of humanistic philosophy and social philosophy, as well as qualitative, analytical, synthetic, comparative, and vice versa. The result is that the subject satisfies his capacity and needs through different activities and lifestyles. Respecting personal life is respecting differences in tradition, culture, religion, beliefs, occupation, and job position. The purpose, method, and results achieved by the author can lead to the conclusion that personal life is human communication. The capacity of an individual is the need of another individual. Mutual satisfaction between individuals is the ultimate happiness of life. In globalization, individuals have many opportunities to assert their abilities and needs, but at the same time, each faces challenges.